Implementasi Nilai-Nilai Moderasi Beragama dalam Konteks Pemberitaan Injil di Indonesia: Pendekatan Harmoni dan Dialog Antaragama - Panjaitan, Juanda; Setiawan, David Eko (Sekolah Tinggi Teologi Berita Hidup, 2025)
This article discusses the implementation of religious moderation values in the context of Gospel proclamation in Indonesia as part of Christianity's approach to maintaining harmony and interfaith dialogue. This study aims to examine how Christianity carries out its mission of evangelism in a way that reflects love and avoids potential conflicts, using a descriptive-analytical approach. Gospel proclamation grounded in love emphasizes an inclusive attitude and respect for differing beliefs without compromising one's own faith. Through principles of justice, balance, tolerance, and compassionate leadership, this study finds that Christianity has the potential to create harmony within religious diversity and to encourage a more robust process of religious moderation in Indonesia.